2019
DOI: 10.2334/josnusd.18-0301
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a universal adhesive for repair bonding to composite and amalgam

Abstract: The study aimed to compare the repair bond strength of aged composite and amalgam repaired with resin composite after various mechanical and adhesive surface treatments. Specimens were aged by thermal cycling (10,000 cycles, 5-55°C) and randomly subjected to one of three surface treatments: diamond bur abrasion, aluminum oxide air abrasion, or silica coating. Conventional bonding or a universal adhesive with incorporated silane was applied afterward (each n = 16) and resin composite was attached. In the contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 31 publications
0
6
1
Order By: Relevance
“…The results of the studies indicate that the application of adhesive agents under amalgam restoration helps prevent microleakage (33,34). The SEM images show that the adhesion between the amalgam and the adhesive is mechanical and forms as a result of the amalgam's interlacing with the adhesive material protruding into the amalgam (35). In the current study, no significant effects were observed on the surface morphology of Panavia F and Amalgambond Plus from interactions with amalgam.…”
Section: Discussioncontrasting
confidence: 49%
“…The results of the studies indicate that the application of adhesive agents under amalgam restoration helps prevent microleakage (33,34). The SEM images show that the adhesion between the amalgam and the adhesive is mechanical and forms as a result of the amalgam's interlacing with the adhesive material protruding into the amalgam (35). In the current study, no significant effects were observed on the surface morphology of Panavia F and Amalgambond Plus from interactions with amalgam.…”
Section: Discussioncontrasting
confidence: 49%
“…Additionally, it has been and amalgam repairs are equally effective as total replacements in terms of clinical success and can therefore, increase restoration longevity following a minimally invasive treatment concept. 1,15 The bond strength of universal adhesives in composite repair is improved by conditioning with aluminum oxide powder air abrasion and silane, according to research on air abrasion by Kuşdemir et al 20 Giannini et al, 21 in a study concluded that when adhesive systems are used to repair amalgam restorations, roughening an old amalgam surface is an essential step and the simple use of a diamond bur can roughen old amalgam. Dieckmann et al 3 in their study found that air abrasion and bur abrasion seem to be equally effective as mechanical surface pretreatment, which is in accordance with the finding in this study because both mechanical surface pretreatment had acceptable results.…”
Section: Resultsmentioning
confidence: 99%
“…HEMA is a hydrophilic material which can decrease the surface tension, besides the increasing amount of HEMA result in increasing SBS, 40% of HEMA for nonprecious metal, and 30% for precious metal(1). Also, low viscosity of ABU might be related to better wettability of amalgam, and consequently higher SBS value (32).…”
Section: Discussionmentioning
confidence: 99%